Evolution and significance of the Lon gene family in Arabidopsis organelle biogenesis and energy metabolism - Rigas, Stamatis; Daras, Gerasimos; Tsitsekian, Dikran; Alatzas, Anastasios; Hatzopoulos, Polydefkis (Frontiers in Plant Science, 2014)
Lon is the first identified ATP-dependent protease highly conserved across all kingdoms. Model plant species Arabidopsis thaliana has a small Lon gene family of four members. Although these genes share common structural features, they have distinct properties in terms of gene expression profile, subcellular targeting and substrate recognition motifs. This supports the notion that their functions under different environmental conditions are not necessarily redundant. This article intends to unravel the biological role of Lon proteases in energy metabolism and plant growth through an evolutionary perspective. Given that plants are sessile organisms exposed to diverse environmental conditions and plant organelles are semi-autonomous, it is tempting to suggest that Lon genes in Arabidopsis are paralogs. Adaptive evolution through repetitive gene duplication events of a single archaic gene led to Lon genes with complementing sets of subfunctions providing to the organism rapid adaptability for canonical development under different environmental conditions. Lon1 function is adequately characterized being involved in mitochondrial biogenesis, modulating carbon metabolism, oxidative phosphorylation and energy supply, all prerequisites for seed germination and seedling establishment. Lon is not a stand-alone proteolytic machine in plant organelles. Lon in association with other nuclear encoded ATP-dependent proteases builds up an elegant nevertheless, tight interconnected circuit. This circuitry channels properly and accurately, proteostasis and protein quality control among the distinct subcellular compartments namely mitochondria, chloroplasts and peroxisomes.